Pengobatan Gratis Pada Kesehatan Masyarakat Lansia di RW 01 Desa Pasir Jambu Sukaraja Bogor - Triswanti; Krisna Dwiyanti (Yayasan Pemimpin Inovasi Science, 2025)
The provision of free medical treatment for the elderly is a critical health issue in Indonesia. The elderly population is particularly vulnerable to disease and poor health outcomes, yet many individuals lack access to adequate medical care. This is attributed to various factors, including poverty, limited access to healthcare facilities, and a lack of knowledge about health. A community service activity was conducted in collaboration with midwives, academics, students, community health workers, and partners from the Yayasan Rumah Yatim Lembaga Amil Zakat Indonesia from Jakarta, with the theme of providing free medical treatment for elderly community health. The objective of this activity was to maintain the health and well-being of the elderly population, enabling them to live a healthy, quality, and productive life. The methodology employed involved several activities, including data collection, blood pressure checks, blood sugar and cholesterol tests, counseling, and health education for the elderly, as well as the provision of free medication according to their needs. This activity was carried out on August 22, 2024, at Rw 01, Pasir Jambu Village, Sukaraja District, Bogor Regency. The outcome of the free medical treatment activity for elderly community health was that the elderly participants gained a better understanding of their health condition, learned about the importance of proper nutrition and diet management, and received free medication according to their needs. The success of this activity can be attributed to the effective collaboration between medical personnel, academics, students, community health workers, and partners from Yayasan Rumah Yatim Lembaga Amil Zakat Indonesia from Jakarta in improving the welfare of the elderly population.